Development and evaluation of recombinant Varicella-Zoster virus glycoprotein E protein microneedles for enhanced pediatric vaccine delivery - Da-Eun Lee; Hye-Ran Cha; Ye-Lim Lee; Hyeon Woo Chung; Sunghoon Park; Yu-Jeong Oh; Eunjung Jung; Seung-Ki Baek; Byung Cheol Ahn; Jung Sun Yum; Jae Myun Lee; Jung-Hwan Park (Drug Delivery and Translational Research, 2026)

Integrated hydroprocessing and microbial biotransformation of coconut oil to α,ω-diacids - Bashu Dev Pardhe; Il-Ho Choi; Chang Hoon Lee; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Hwabong Jeong; Jongbeom Park; Kyung Taek Heo; et al. (Bioresource Technology, 2025)

Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Impact of thawing methods and packaging sizes on the physicochemical and microbial quality of frozen kimchi - Hee Eun Kim; Yun-Jeong Choi; Dong Hyun Park; Min Jung Lee; Minji Kim; Sung Jin Park; Ji Young Choi; Mi Ran Kang; Sung Hee Park; Mi-Ai Lee (International Journal of Refrigeration, 2025)

Deciphering the links: Fragmented polystyrene as a driver of skin inflammation - Gyeong Bae Song; Jisoo Nam; Sangmin Ji; Gijeong Woo; Soojeong Park; Bokyung Kim; Jeein Hong; Myung Gil Choi; Seokheon Kim; Chaerin Lee; Wonchul Lim; Sangwoon Yoon; et al. (Journal of Hazardous Materials, 2024)

Nitric acid modified powdered activated carbon for simultaneous adsorption of lead and phenol in aqueous solution - Hyun-Kyung Kim; So-Jeong Kim; Hye-Ran Kim; Jae-Woo Park (Journal of Environmental Chemical Engineering, 2024)

Safety of applying influenza-antigen-coated microneedles to rat skin and the antigen specific immune response in vivo - Taek-Seon Yun; Bomin Song; Yu-Rim Hwang; Minki Jin; Hyeseung Seonwoo; Donki Kim; Hye Won Kim; Byeong Cheol Kim; Daekyung Kim; Boyeong Park; Jeong Yeon Kang; Seung-Ki Baek; et al. (Journal of Pharmaceutical Investigation, 2024)

Lysolecithin-fatty acid liposomes as novel antibacterial agents to suppress the growth of periodontal Porphyromonas gingivalis - Jeong-Hoo Lee; Hyo-Ran Lee; Yeeun Park; Hye-Seong Lee; Jiyoung Hwang; Gyuwhan Lee; Hye-Sung Kim; Inseong Hwang; Jin-Byung Park (Food Bioscience, 2024)

RETRACTED ARTICLE: T1 transgenic tobacco plants carrying multicopy T-DNAs at the same locus exhibit various expression levels of transgenes - Sung Ran Min; Seyed Javad Davarpanah; Youn-il Park; Jae Heung Jeon; Jae Sun Moon; Jang Ryol Liu; Won Joong Jeong (Plant Biotechnology Reports, 2023)

Radiological Investigation of Gas Embolism in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) - Adams Hei Long Yuen; Sang Wha Kim; Sung Bin Lee; Seyoung Lee; Young Ran Lee; Sun Min Kim; Cherry Tsz Ching Poon; Jun Kwon; Won Joon Jung; Sib Sankar Giri; Sang Guen Kim; Jeong Woo Kang; et al. (Frontiers in Marine Science, 2022)
Cetaceans have long been considered biologically adapted to suffer no adverse effects from diving-related tissue gas tension. However, increasing reports of gas embolism in cetaceans inhabiting European, Mediterranean and American waters have challenged the conventional understanding of marine mammal diving physiology. In human hyperbaric medicine, virtopsy techniques such as post-mortem computed tomography (PMCT) facilitate the visualization of gas embolism and could be performed adjunct to conventional autopsy. This research presents the first case of gas embolism identified in an East Asian finless porpoise inhabiting Asian waters. Massive gas embolic lesions were found in the liver, which had been compressing both the lungs and abdominal organs, and signs of pneumonia and parasitic infection were observed in both lungs. It is hypothesized that this porpoise might have been unable to expel in vivo gas bubbles from its circulation due to pulmonary dysfunction. Consequently, gas bubbles agglomerated in the liver, resulting in the development of gas embolic lesions. The findings of the present study provide insights into the occurrence of gas embolism in the East Asian finless porpoise, highlighting the potential of PMCT as a promising tool for the diagnosis of gas embolism in stranded cetaceans.

Ovalbumin and cholera toxin delivery to buccal mucus for immunization using microneedles and comparison of immunological response to transmucosal delivery - Yu-Jeong Oh; Hye-Ran Cha; Su Jin Hwang; Dae-Sung Kim; Yu-Ji Choi; Yun-Seo Kim; Yu-Ra Shin; Thuy Trang Nguyen; Seong-O Choi; Jae Myun Lee; Jung-Hwan Park (Drug Delivery and Translational Research, 2021)

The chemical constituents of ethanolic extract from Stauntonia hexaphylla leaves and their anti-inflammatory effects - Le Ba Vinh; Se Jin Jo; Phong Nguyen Viet; Dan Gao; Kyoung Won Cho; Eun-Jeong Koh; Sung Sun Park; Young Ran Kim; Young Ho Kim; Seo Young Yang (Natural Product Research, 2021)

Enhanced tolerance to heat stress in transgenic tomato seeds and seedlings overexpressing a trehalose-6-phosphate synthase/phosphatase fusion gene - Jae Il Lyu; Ji Hyun Park; Ju-Kon Kim; Chang-Hyu Bae; Won-Joong Jeong; Sung Ran Min; Jang R. Liu (Plant Biotechnology Reports, 2018)

Characterization of high temperature-tolerant strains of Pyropia yezoensis - Yoon Ju Shin; Sung Ran Min; Da Yeon Kang; Jong-Min Lim; Eun-Jeong Park; Mi Sook Hwang; Dong-Woog Choi; Joon-Woo Ahn; Youn-Il Park; Won-Joong Jeong (Plant Biotechnology Reports, 2018)

l-carnosine induces apoptosis/cell cycle arrest via suppression of NF-κB/STAT1 pathway in HCT116 colorectal cancer cells - Jooyeon Lee; Jeong-Ran Park; Hanbyeol Lee; Soojin Jang; Se-Min Ryu; Hyejin Kim; Donguk Kim; Aera Jang; Se-Ran Yang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Complete mitochondrial genome of the beluga whale Delphinapterus leucas (Cetacea: Monodontidae) - Ji Hyung Kim; Young-Ran Lee; Jeong-Rack Koh; Jin Woo Jun; Sib Sankar Giri; Hyoun Joong Kim; Cheng Chi; Saekil Yun; Sang Geun Kim; Sang Wha Kim; Hye Kwon Kim; Dae Gwin Jeong; et al. (Conservation Genetics Resources, 2017)

Characterization of PyGUS gene silencing in the red macroalga, Pyropia yezoensis - Yoon Ju Shin; Jong-Min Lim; Ji Hyun Park; Dong-Woog Choi; Mi Sook Hwang; Eun-Jeong Park; Sung Ran Min; Suk Weon Kim; Won-Joong Jeong (Plant Biotechnology Reports, 2016)

Thiacremonone Potentiates Anti-Oxidant Effects to Improve Memory Dysfunction in an APP/PS1 Transgenic Mice Model - Hyung-Mun Yun; Peng Jin; Kyung-Ran Park; JaeRyun Hwang; Heon-Sang Jeong; Eun-Cheol Kim; Jea-Kyung Jung; Ki-Wan Oh; Bang Yeon Hwang; Sang Bae Han; Jin Tae Hong (Molecular Neurobiology, 2016)

Functional characteristics of mesenchymal stem cells derived from the adipose tissue of a patient with achondroplasia - Jeong-Ran Park; Hanbyeol Lee; Chung-Hyo Kim; Seok-Ho Hong; Kwon-Soo Ha; Se-Ran Yang (In Vitro Cellular & Developmental Biology - Animal, 2016)

An episomal vector system for plastid transformation in higher plants - Sung Ran Min; Seyed Javad Davarpanah; Seo Hee Jung; Youn-il Park; Jang R. Liu; Won-Joong Jeong (Plant Biotechnology Reports, 2015)

Endosulfan induces COX-2 expression via NADPH oxidase and the ROS, MAPK, and Akt pathways - Hyung Gyun Kim; Young Ran Kim; Jin Hee Park; Tilak Khanal; Jae Ho Choi; Minh Truong Do; Sun Woo Jin; Eun Hee Han; Young Ho Chung; Hye Gwang Jeong (Archives of Toxicology, 2015)

Isolation of human dermis derived mesenchymal stem cells using explants culture method: expansion and phenotypical characterization - Jeong-Ran Park; Eunjeong Kim; Jungwon Yang; Hanbyeol Lee; Seok-Ho Hong; Heung-Myong Woo; Sung-Min Park; Sunghun Na; Se-Ran Yang (Cell and Tissue Banking, 2015)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Nicotine inhibits the proliferation by upregulation of nitric oxide and increased HDAC1 in mouse neural stem cells - Hanbyeol Lee; Jeong-Ran Park; Jungwon Yang; Eunjeong Kim; Seok-Ho Hong; Heung-Myong Woo; Se-Min Ryu; Sung-Joon Cho; Sung-Min Park; Se-Ran Yang (In Vitro Cellular & Developmental Biology - Animal, 2014)

ENA-A actimineral resource A extends lifespan associated with antioxidant mechanism in SMP30 knockout mice - Jung-Youn Han; Meeyul Hwang; Sung-Yong Hwa; Jin-Kyu Park; Mi-Ran Ki; Il-Hwa Hong; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Chang-Woo Min; Kyung-Ku Kang; Myeong-Mi Lee; et al. (Molecular and Cellular Biochemistry, 2014)

Synechocystis PCC6803 and PCC6906 dnaK2 expression confers salt and oxidative stress tolerance in Arabidopsis via reduction of hydrogen peroxide accumulation - Jonghyun Kim; Myung Suk Ahn; Young Min Park; Suk Weon Kim; Sung Ran Min; Weon Joong Jeong; Jang R. Liu (Molecular Biology Reports, 2014)

Thymol from Thymus quinquecostatus Celak. protects against tert-butyl hydroperoxide-induced oxidative stress in Chang cells - Yon-Suk Kim; Jin-Woo Hwang; Seo-Hee Kang; Ee-Hwa Kim; You-Jin Jeon; Jae-Hyun Jeong; Hye-Ran Kim; Sang-Ho Moon; Byong-Tae Jeon; Pyo-Jam Park (Journal of Natural Medicines, 2014)

(E)-2,4-Bis(p-hydroxyphenyl)-2-butenal inhibits tumor growth via suppression of NF-κB and induction of death receptor 6 - Jung Ok Ban; Young-Suk Jung; Dae Hwan Kim; Kyung-Ran Park; Hyung-Mun Yun; Nam Jin Lee; Hee Pom Lee; Jeong-Hyun Shim; Heon-Sang Jeong; Yun-Hee Lee; Young Wan Ham; Sang-Bae Han; et al. (Apoptosis, 2014)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Stable Plastid Transformation in Nicotiana benthamiana - Seyed Javad Davarpanah; Seo Hee Jung; Yaw Joo Kim; Youn-Il Park; Sung Ran Min; Jang Ryol Liu; Won Joong Jeong (Journal of Plant Biology, 2009)

Effects of bio-active ceramic resources in cutaneous wound healing and the role of TGF-β signaling - Jae-Yong Chung; Sun Hee Do; Won-Il Jeong; Da-Hee Jeong; Sang-Joon Park; Mi-Ran Ki; Dong-Mi Kwak; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Up-regulation of Metabotropic glutamate receptor 3 (mGluR3) in rat fibrosis and cirrhosis model of persistent hypoxic condition - Sun Hee Do; Hae-Sun Yun; Won-Il Jeong; Da-Hee Jeong; Mi-Ran Ki; Jae-Yong Chung; Sang-Joon Park; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

The complete chloroplast genome sequences of Solanum tuberosum and comparative analysis with Solanaceae species identified the presence of a 241-bp deletion in cultivated potato chloroplast DNA sequence - Hwa-Jee Chung; Jong Duk Jung; Hyun-Woo Park; Joo-Hwan Kim; Hyun Wook Cha; Sung Ran Min; Won-Joong Jeong; Jang Ryol Liu (Plant Cell Reports, 2006)

An α3β4 subunit combination acts as a major functional nicotinic acetylcholine receptor in male rat pelvic ganglion neurons - Kyu-Sang Park; Seung-Kyu Cha; Min-Jeong Kim; Dae-Ran Kim; Seong-Woo Jeong; Joong-Woo Lee; In Deok Kong (Pflügers Archiv - European Journal of Physiology, 2006)